Dorsal Wrist Capsular Tears in Association with Scapholunate Instability: Results of an Arthroscopic Dorsal Capsuloplasty - Binder, Adeline Cambon; Kerfant, Nathalie; Wahegaonkar, Abhijeet L.; Tandara, Andrea A.; Mathoulin, Christophe L. (Journal of Wrist Surgery, 2013)
Purpose The purpose of this study is to report the association of dorsal wrist capsular avulsion with scapholunate ligament instability and to evaluate the results of an arthroscopy-assisted repair.Methods We retrospectively reviewed 10 patients with a mean age of 39.1 years suffering from chronic dorsal wrist pain. They underwent a wrist arthroscopy with an evaluation of the scapholunate ligament complex from the radiocarpal and midcarpal compartments. An avulsion of the dorsal intercarpal ligament (DICL) from the scapholunate interosseous ligament (SLIL) was visible from the radiocarpal compartment in all cases, while the SLIL was intact. The DICL tear was repaired with an arthroscopy-assisted dorsal capsuloplasty. Patients were assessed preoperatively and postoperatively by the QuickDASH (Disabilities of the Arm, Shoulder, and Hand) questionnaire, by the Visual Analog Scale (VAS) for pain, and by a clinical and radiological examination.Results Preoperatively, all patients had reduced flexion and radial deviation of the affected wrist. On the lateral radiograph, 5 of the 10 patients showed an increase of the scapholunate angle (60 to 85°). The scapholunate instability was graded as Messina–European Wrist Arthroscopy Society (EWAS) II in five cases and as grade IIIB in five cases. A tear of the ulnar part of the triangular fibrocartilage complex (TFCC) was found in seven cases. At a mean followup of 16 months, the wrist range of motion (ROM), the grip strength, the QuickDASH, and the VAS of pain improved significatively. The scapholunate angle was normalized in all cases.Discussion Isolated tears of the DICL at its insertion from the dorsal part of the SLIL can be associated with scapholunate instability in the absence of an injury to the SLIL. The diagnosis is made arthroscopically. The arthroscopic dorsal capsuloplasty is a minimally invasive technique that provides short-term satisfactory results. Further studies are needed to determine whether repair of the DICL tear could prevent secondary destabilization of the scapholunate ligament complex.Level of evidence IV (case series) Diagnosis
Keywords: dorsal intercarpal ligament; scapholunate instability; scapholunate ligament; wrist arthroscopy; dorsal capsulodesis